The inter-relationship of gastro-enteritis and malnutrition in Cape Town - Wittmann, W (Department of Medicine, 2024)
Diarrhoea is an important cause of illness throughout the world and remains a leading cause of death among infants and young children. The number of deaths from this condition is estimated at 5 million a year. There are important clinical differences in the disease as it manifests itself in previously normal well-nourished children compared with malnourished children. The major part of the total world problem today is concentrated in the industrially underdeveloped countries where malnutrition and retarded development are a feature of infancy and early childhood. In a recent review Ordway indicated the emphasis that is put on (1) the high morbidity and mortality rates among infants and young children, (2) the association with malnutrition, (3) the low socio-economic status of the affected population groups and (4) the multiple and often obscure aetiology of the disease. In this review special emphasis will be put on the association of the disease with malnutrition, where morbidity and mortality are highest. Accurate morbidity figures are not always available but where mortality is high, morbidity is also high.